RECONSTRUCTION OF PAI LEARNING THROUGH THE LOVE CURRICULUM: PAI TEACHERS' STRATEGIES IN INTERNALIZING THE VALUES OF RELIGIOUS MODERATION AND STUDENT WELL-BEING - Nurun Nafisah Indah Qomari; Moch. Tohet (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to reconstruct Islamic Religious Education (PAI) through a Love-Based Curriculum as a practical strategy to integrate Aqidah Akhlak values, religious moderation, and students’ psychological well-being at MI Darul Hikmah Al-Fatimiyah. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation analysis, and then analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings indicate that the Love-Based Curriculum is not only implemented through teacher–student interaction but is also institutionalized within instructional documents and the cultural system of the school. At the practical level, teachers apply compassion-oriented pedagogy in Aqidah Akhlak learning through personal greetings, empathetic narratives, and emotional reflection. At the institutional level, compassion-based values are integrated into lesson plans, character reports, and school activities such as Salam Kasih Sayang and collective prayer. This implementation has proven effective in fostering moderate character, enhancing social empathy, and strengthening students’ emotional well-being. The study concludes that the Love-Based Curriculum serves as an alternative instructional model for PAI that is relevant for addressing issues of intolerance and the empathy crisis in Islamic elementary education.